STRATEGI PENINGKATAN KINERJA KARYAWAN MELALUI PROGRAM PELATIHAN DAN MOTIVASI KERJA DI PT. FORUM BISNIS SEJAHTERA - Prayoga, Dimas Drajat Bambang; Ikhwan, Khairul (Transpublika Publisher, 2023)
This study aims to find out how the strategies used by PT Forum Bisnis Sejahtera in improving employee performance in the company. Given the importance of the role of HR in the company, companies are required to provide training and development as well as work motivation for all employees, so that employee performance increases and work can be completed effectively and efficiently. This study uses an interpretative qualitative method by conducting direct interviews with the relevant informants. Sources of data in this study are primary data and secondary data. Primary data were taken from interviews with PT Forum Bisnis Sejahtera. In general, the results show that PT Forum Bisnis Sejahtera already has the right strategy in improving the performance of its employees. The strategy by providing training and work motivation can support employee performance. Providing training is very important for companies, because with the training and motivation provided, employees can improve the abilities, skills, and skills possessed by each employee. The motivation given by the company can also improve employee performance.